Види гвоздичних (Caryophyllaceae Juss.) як перспективні декоративні рослини - Fedoronchuk, M.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The data about willd and cultivated species of Caryophyllaceae Juss. with high ornamental peculiarities which proposed to introduction are presented.